AB0238 SERUM LEVELS OF E-SELECTIN AND IL-8 DECREASE AFTER 6 MONTHS OF ANTI-INFLAMMATORY THERAPY AND MIRROR FAVORABLE VASCULAR CHANGES IN RHEUMATOID ARTHRITIS. (2nd June 2020) - Blanken, A.; Agca, R.; Popa, C. D.; Nurmohamed, M.
Abstract : Background: Accelerated atherosclerosis is a systemic manifestation of rheumatoid arthritis (RA). E-selectin, VCAM-1, MCP1/CCL2 and IL-8/CXCL8 are involved in leukocyte migration through endothelial cells in both atherosclerosis and RA [1]. Therefore, these endothelial function markers might reflect endothelial function and systemic inflammation in RA. If so, such a marker could be used to assess cardiovascular risk in RA patients. Objectives: The aim of this study was to investigate the effect of 6 months of anti-inflammatory treatment on RA serum levels of endothelial function markers and whether these serum levels are related to prognostic imaging markers for atherosclerosis. Methods: E-selectin, VCAM-1, MCP1 and IL-8 serum levels were determined at baseline and after 6 months of therapy with MTX monotherapy or in combination with adalimumab for 40 RA patients and 19 osteoarthritis (OA) controls using commercial ELISA kits. Prognostic imaging markers for atherosclerosis were pulse wave velocity (PWV) and augmentation index (AIx) as measured with SphygmoCor tonometry. Parametric analyses were used for E-selectin, VCAM-1 and MCP1 and non-parametric or parametric analyses after log transformation for IL-8. Results: Baseline VCAM-1 and IL-8 were significantly higher for RA patients than OA controls with and without adjustment for age and sex or traditional risk factors (table 1 ). After 6 months of anti-inflammatory therapy, E-selectin and IL-8 serum levels significantly decreased (table 2 ). This decrease was especially present in the RA patients with good EULAR-DAS28 response to the medication and not in patients with no/moderate response (E-selectin: -7, 95%CI -13- -2, p=0.007 versus -0.1, 95%CI -3-2, p=0.925; IL-8: -2, p=0.033 versus -1, p=0.267). Furthermore, in the RA patients we found a significant correlation between the difference in PWV after 6 months and the difference in E-selectin (Pearson r=0.450, p=0.018) and IL-8 (Spearman r=0.401, p=0.038). All other possible correlations of the endothelial function markers with PWV and AIx were not significant (data not shown). Conclusion: Serum levels of E-selectin and IL-8 decreased after 6 months of anti-inflammatory therapy, and both correlated with the PWV changes. This is the first study investigating both serologic as well as imaging markers of endothelial function and atherosclerosis in RA patients undergoing anti-inflammatory therapy. Our study suggests that E-selectin and IL-8 circulatory levels may reflect the best both systemic inflammation as well as endothelial function in RA, and might be therefore useful in the future as markers of cardiovascular risk in these patients. References: [1]Haringman et al. Targeting cellular adhesion molecules, chemokines and chemokine receptors in rheumatoid arthritis. Expert Opin Emerg Drugs, 2005. 10(2): p. 299-310. Disclosure of Interests: Annelies Blanken: None declared, Rabia Agca: None declared, C.D. Popa: None declared, Michael Nurmohamed Grant/research support from: Not related to this research, Consultant of: Not related to this research, Speakers bureau: Not related to this research